THE INFLUENCE OF HEAT ACTIVATION AND CU ADDITION ON ZEOLITE TOWARDS THE ANTIMICROBIAL AFFECT ON STAPHYLOCOCCUS AUREUS - Siti Sunarintyas; Harsini Harsini; Noor Hafida Widyastuti; Christine Windayani Inan (Faculty of Dentistry, Universitas Indonesia, 2015)
Zeolite is a pore mineral occupied by ions and water molecules. Heat activation of zeolite causes the release of water molecules, from the pores and increases zeolite adsorbance capacity. Zeolite can be used as an antimicrobial agent by shifting its cation with other cation that has antimicrobial effect. The aim of this research is to determine the influence of heat activation and Cu addition on zeolite towards its antimicrobial effect on Staphylococcus aureus. There were 5 groups for heat activation of zeolite experiment: room temperature (100°C, 200°C, 300°C, and 400°C). Using effective heat activation temperature, the research was continued to determine the effect of Cu addition on Staphylococcus aureus growth. There were 4 groups of Cu concentration addition on zeolite: 0.025 M, 0.05 M, 0.1 M, and 0.2 M. Antimicrobial test of Cu-zeolite was determined by diffusion method. The data was analyzed by using Anova and LSD. The result showed that there was a significant difference among various zeolite heat activation toward Staphylococcus aureus growth (p<0.05). In conclusion, zeolite heat activation up to 400°C and the addition of Cu on zeolite up to 0.2 M influence the antimicrobial affect on Staphylococcus aureus.